Приклад

Обчислити \({\int \int}_{D} e^{-x^2-y^2} dxdy\)
де D є круг радіуса R з центром у початку координат: \(x^2+y^2\leq R^2.\)
Розв'язання:
Зробимо замінну змінних: \(x=\rho\cos \varphi, \;y=\rho\sin \varphi\) тоді рівняння \(x^2+y^2\leq R^2.\) перетвориться на \(\rho=R(0\leq \varphi\leq 2\pi).\) Тоді за формулою : $${\int \int}_{D} f(x, y) dxdy={\int \int}_{D} f(\rho \cos \varphi,\;\rho \sin \varphi) \rho d\rho d \varphi$$
маємо: $${\int \int}_{D} e^{-x^2-y^2} dxdy=\left|\matrix{x=\rho\cos \varphi,& D\rightarrow D',\\ y=\rho\sin \varphi,& D':0\leq\rho\leq R,\\dxdy=\rho d \rho d \varphi,&0\leq \varphi\leq 2\pi}\right|=$$ $$={\int \int}_{D} e^{-\rho^2} \rho d \rho d \varphi=\int_{0}^{2\pi}{d \varphi}\int_{0}^{R}{ e^{-\rho^2} \rho d \rho}=$$ $$=\int_{0}^{2\pi}\left( \int_{0}^{R}{ e^{-\rho^2} \rho d \rho}\right) d \varphi=\int_{0}^{2\pi}\left(-\frac{1}{2}\int_{0}^{R}{ e^{-\rho^2} d (-\rho^2)} \right)d \varphi=$$ $$=-\frac{1}{2}\int_{0}^{2\pi}\left( e^{-\rho^2}\mid_{0}^{R}\right) d \varphi = -\frac{1}{2}\int_{0}^{2\pi}\left( e^{-R^2}-1\right)d \varphi=$$ $$=\frac{1-e^{-R^2}}{2}\int_{0}^{2\pi}{d \varphi}=\pi\left(1- e^{-R^2}\right).$$


2012-12-20 • Просмотров [ 514 ]